Vets and Vaccines: A Discursive Analysis of Pet Vaccine Critique - Hobson-West, Pru (Frontiers in Veterinary Science, 2022)
Critique of vaccination policy and practice has a long history, and social scientists and others have devoted significant efforts to understanding this phenomenon. This attention has only increased in light of the coronavirus pandemic, with public health concerns expressed about opposition to vaccination strategies. However, much less attention has thus far been devoted to understanding veterinary vaccine critique. This is problematic, given the central role of animals in the production and consumption of vaccines, and the existence of veterinary professional anxiety and international media coverage. The lack of existing literature may reflect a wider paucity of research on the veterinary profession; a paucity actively being challenged by new fields of veterinary anthropology and sociology. This short report is based on a discourse analysis of a UK campaign group, which questions aspects of companion animal vaccine policy. Findings suggest that the kinds of discourses used are similar to those made in the human vaccine domain: questions of risk, trust in expertise and imaginaries of science are thus not unique to human medicine. However, the article argues that some of the discourses identified are actually in line with wider social and cultural developments in healthcare. This argument has potential implications for veterinary professionals, as well as scholars interested in animal or human medicine. The article concludes by identifying future research trajectories, focused on further analysis of discursive practice, or the use of ethnographic observation to more fully understand the relationship between humans and non-humans, including animals and vaccine technologies.